Note su alcuni termini dei testi amministrativi di Ebla - Pomponio, F.
ersch. 1984; DILMUN-ku5 'periodical laborers'; ga-du8 'nurse'; ḫar-zú/ru11-ba-tum 'a decoration'; zà-me 'are ready'; zi-bar 'a receptacle'.